Navigating the brain: the role of exosomal shuttles in precision therapeutics - Fatima, Shaheera; Qaiser, Ariba; Andleeb, Saadia; Hashmi, Asraf Hussain; Manzoor, Sobia (Frontiers in Neurology, 2024)
Brain diseases have become one of the leading roots of mortality and disability worldwide, contributing a significant part of the disease burden on healthcare systems. The blood-brain barrier (BBB) is a primary physical and biological obstacle that allows only small molecules to pass through it. Its selective permeability is a significant challenge in delivering therapeutics into the brain for treating brain dysfunction. It is estimated that only 2% of the new central nervous system (CNS) therapeutic compounds can cross the BBB and achieve their therapeutic targets. Scientists are exploring various approaches to develop effective cargo delivery vehicles to promote better therapeutics targeting the brain with minimal off-target side effects. Despite different synthetic carriers, one of the natural brain cargo delivery systems, “exosomes,” are now employed to transport drugs through the BBB. Exosomes are naturally occurring small extracellular vesicles (EVs) with unique advantages as a therapeutic delivery system for treating brain disorders. They have beneficial innate aspects of biocompatibility, higher stability, ability to cross BBB, low cytotoxicity, low immunogenicity, homing potential, targeted delivery, and reducing off-site target effects. In this review, we will discuss the limitations of synthetic carriers and the utilization of naturally occurring exosomes as brain-targeted cargo delivery vehicles and highlight the methods for modifying exosome surfaces and drug loading into exosomes. We will also enlist neurodegenerative disorders targeted with genetically modified exosomes for their treatment.